ANALYSIS OF PRODUCT DEVELOPMENT IN INDUSTRIAL ENTERPRISES ON THE BASIS OF EFFICIENT USE OF LOCAL RESOURCES (BY KASHADARYO REGION) - Izbasarov Bahadir Ergashovich (American Journals, 2024)
This article describes the dynamics of the volume of industrial products in the territory of Kashkadarya region and the rate of growth of industrial production. It talks about the development of industrial enterprises, macroeconomic stability, the well-being of the population and prevention of unemployment. Also, the production of products in the industrial enterprises in the territory of Kashkadarya region was theoretically compared between regions. Kashkadarya Region analyzed the dynamics of the volume of industrial products and growth rates of industrial products production by region. The author has studied the reasons for the decrease of the efficiency index in some districts and made conclusions.
Keywords: economic growth, productivity, economic efficiency, labor productivity, industrial output, gross domestic product, imports, exports.